2014
DOI: 10.1002/jbm.b.33353
|View full text |Cite
|
Sign up to set email alerts
|

Titanium implant impairment and surrounding muscle cell death following neuro‐myoelectrostimulation: An in vivo study

Abstract: Electrical currents have deleterious effects on biomedical metallic implants. However, following arthroplasty, neuro-myoelectrostimulation (NMES) is often used in patient rehabilitation. Such a rehabilitation technique could compromise patient recovery through deleterious effects on metallic alloys and biological tissues. The purpose of our study was to assess the effects of NMES on a Ti6Al4V implant placed in a rat tibial crest and the surrounding muscle tissues. This in vivo study allowed to bring to the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Contrary to Ti‐Es group, the pull‐out test revealed no significant adhesion strength reduction when NMES was applied for PEEK, Al 2 O 3 and CrCo. In a previous study, we have already demonstrated that an electrical stimulation applied to the muscles surrounding a titanium implant drastically decreased the implant‐to‐bone adhesion . A possible explanation of this result may be found in the properties of Ti6Al4V implant which can be compared with an electrode propagating electrical current to the surrounding tissues .…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Contrary to Ti‐Es group, the pull‐out test revealed no significant adhesion strength reduction when NMES was applied for PEEK, Al 2 O 3 and CrCo. In a previous study, we have already demonstrated that an electrical stimulation applied to the muscles surrounding a titanium implant drastically decreased the implant‐to‐bone adhesion . A possible explanation of this result may be found in the properties of Ti6Al4V implant which can be compared with an electrode propagating electrical current to the surrounding tissues .…”
Section: Discussionmentioning
confidence: 88%
“…Thus, a metal implant in the vicinity of the electrical stimulation area could act as an electrode facilitating the spread of the electric current in the biological tissues. In a previous study, we showed a higher cell death rate on two muscles located in the vicinity of a Ti6Al4V implant fixed on rat tibial crest after two weeks of NMES program . The implant‐to‐bone adhesion was also decreased with the application of electrical stimulation, probably due to wear debris NMES‐induced .…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations